2022
DOI: 10.1371/journal.pone.0273892
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in meningeal lymphatic endothelial cells following traumatic brain injury in mice

Abstract: Meningeal lymphatic vessels transport both the cerebrospinal fluid and interstitial fluid to the deep cervical lymph nodes. Traumatic brain injury (TBI) is accompanied by meningeal injury. We hypothesized that the TBI-induced meningeal injury would damage lymphatic vessels and affect brain function. We observed altered gene expression in meningeal lymphatic endothelial cells (LECs) in a mouse model of TBI. Through flow cytometry–based cell sorting, meningeal LECs were obtained from a mouse model of controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The JAK/STAT signalling pathway is a critical factor promoting neuroin ammation in neurodegenerative diseases such as AD [46]. Many studies have reported on the activation of the JAK/STAT pathways in meningeal cells due to meningioma, bacterial infection and traumatic brain injury [47], [48], [49]. Thus, on identifying the cytokines produced by the LMCs in the presence of Aβ, we next investigated the potential involvement of the JAK/STAT pathways in the response of LMCs to the presence of Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK/STAT signalling pathway is a critical factor promoting neuroin ammation in neurodegenerative diseases such as AD [46]. Many studies have reported on the activation of the JAK/STAT pathways in meningeal cells due to meningioma, bacterial infection and traumatic brain injury [47], [48], [49]. Thus, on identifying the cytokines produced by the LMCs in the presence of Aβ, we next investigated the potential involvement of the JAK/STAT pathways in the response of LMCs to the presence of Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, SDH resulted in decreased expression of meningeal lymphatic valve proteins FOXC2 and PROX1, further indicating valvular inadequacy in these dilated basal MLVs. Notably, the dysfunctional MLVs observed in TBI, neurotropic viral infections, and aged mice are also accompanied by decreased expressions of FOXC2 and PROX1 26 , 42 , 43 . Besides the defective valves, we also found disrupted connections between the mLECs in the basal MLVs, which have also been reported in aging and Parkinson's disease 18 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…MRI of a closed-head impact model of engineered rotational acceleration (CHIMERA) shows meningeal enhancement 7d after single and repeat injury, reflecting clinical observations [ 305 ]. Controlled cortical impact (CCI) in mice presents mixed findings: Lyve-1 + morphology is increased at 7 d (impact 1.5 mm) [ 306 ], with contrasting studies showing decreases at 3 d (impact 2 mm) [ 307 ], and 1 month (impact undisclosed) [ 308 ], highlighting the nuanced and variable nature of spontaneous lymphangiogenic responses across varied mechanisms of impact and injury parameters. Regardless, if plasticity of the lymphatic network can be induced, it may be beneficial to improve outcomes (Fig.…”
Section: Meningeal Lymphatic Dysfunction After Tbimentioning
confidence: 99%
“…Revascularization at 3 d, 5 d,7 d. Inhibited by infection At 1 d, 3 d, 4 d and 7 d ↑ CD11b + , CD206 + myeloid cells [ 321 ] 2021 CCI (3 mm, 3 m/s, dwell time 85 ms) Male C57Bl/6J mice (9–10 wks) 1 d, 7 d, 1 year Meninges, Meningeal ILCs (Innate lymphoid cells) At 1,7d ↑ILC1-3. At 1y ↑ILC2/3 Metabolic dysregulation with ↓AMPKα1 at 1d *CCI + IL-33 (1μg) ↑pAMPKα [ 298 ] 2021 CHIMERA (single × 1 & repeat × 4) Male, Female C57Bl/6 mice (6–7 wks) 1 d, 7 d Whole brain MRI At 1d & 7d ↑ meningeal enhancement in both single and repeat impacts [ 305 ] 2022 CCI (0.5 mm or 1 mm, 5 m/s, d well undisclosed) Male C57Bl/6J mice (9–10 wks) 3 dpi, 6 wks Dura mater–RNAseq, Whole mount meninges 3dpi - ↑CD45+ myeloid (B cell) & CD11b+ cells 6 wks - ↑Ccl8, Il1β, Ccl2 Ccl7 ↑immune pathways, including interferon gamma response [ 316 ] 2022 CCI (2 mm, velocity undisclosed) Male C57Bl/6 mice (10 wks) 3 d Meningeal lymphatic endothelial cells (LECs) Flow cytometry ↓ Lyve1 LECs Microarray ↑ DEGs involved in FCERI signaling, antibody-mediated complement, Inflammatory response [ 307 ] 2022 Adapted CCI hit and run (closed head, 2 mm, 5.2 m/s, dwell time 100 ms) Male C57Bl/6J mice (8–12 wks & 20 months) 7 d, 1.5 m Whole mount meninges Meninges for bulk & scRNA-seq At 7d, ↑DEG s related to macrophages, fibroblasts, and adaptive immune cells. ↑IFNβ, IRF5, IFNAR1 At 1.5m ↑ collagen, fibroblasts ↑T/B cell DEG.…”
Section: Meningeal Lymphatic Dysfunction After Tbimentioning
confidence: 99%